Clinico-radiological evaluation of oligohydramnios with special reference to pregnancy outcome - Bhattacharya, Apurba Kumar; Doley, Runjun; Bhattacharjee, Abhinab (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Oligohydramnios is defined as amniotic fluid index of less than 5cm. It is thought to be associated with increased fetal and maternal morbidity. Studies are not clear whether the adverse perinatal outcome merely reflects the sequel of other conditions or if, reduced amniotic fluid volume itself contributes to adverse outcomes. Methods: A total of 150 pregnant women with gestational age >34 weeks having clinically diagnosed oligohydramnios were enrolled in this observational prospective clinical study, during the study period of 12 months,1June 2020 to 31May 2021. Patients were first subjected to ultrasonographic AFI estimation, divided into two groups (oligohydramnios and borderline AFI) and then followed up for maternal and fetal outcome. Data was statistically analyzed. Results: A total 72.66% had AFI less than 5 cm. 97 (64.66%) were primigravida. 68% were prepared for Caesarean section irrespective of gestational period, the most common indication being fetal distress. 66.66% babies had good APGAR score at 1 minute after birth.41.06% delivered babies who required NICU admission, although only 2% neonatal deaths were recorded. Conclusions: Our study shows that isolated decreased AFI after 34 weeks of gestation is associated with satisfactory perinatal outcome. Both groups in the study, when compared statistically, were relatively similar in their pregnancy outcome. Significant association was found between oligohydramnios and increased rate of caesarean section, NICU admission and abnormal fetal heart rate tracing.